Caracterización química de algunos desechos agroindustriales en Costa Rica. - Sibaja B., Rosario (1988)
Agricultural wastes of pineapple peel, saw dust, rice peel, coffee bean pulp skin and parchment, were chemically characterized, and the cellulose and lignin separeted. The I R spectra of these lignocellulosic materials and commercial ones were similar. Water sorption studies showed that the cellulose from agrowastes were more amorphous than those from commercial samples of native and microcrystalline cellulose.